Penerapan Model Kooperatif Tipe TGT Dengan Media Wordwall Untuk Meningkatkan Prestasi Belajar Siswa - Winarni, Intan Wahyu; Pamujo, Pamujo (Jurnal Gentala Pendidikan Dasar, 2026)
This study aimed to improve the science learning achievement of fifth-grade students at SD N 1 Karangnangka through the implementation of the team games tournament cooperative learning model assisted by Wordwall as a learning medium under the theme "My Regional Pride." The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The research was conducted over two cycles and involved 15 students. Data were collected through achievement tests, observations, and documentation and were analyzed descriptively. The findings showed a continuous improvement in students' learning achievement. The average score increased from 71.93 (40% learning mastery) in the pre-cycle to 77.50 (66.67% learning mastery) in Cycle I and 82.00 (80% learning mastery) in Cycle II. In addition, students' learning activities and discussion skills also improved throughout the implementation of the intervention. These findings indicate that the team games tournament cooperative learning model assisted by Wordwall is effective in improving science learning achievement in elementary schools.